2020
DOI: 10.1002/anie.202009138
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐Selective C−H Alumination of Mono‐Substituted Benzene by Using An Alkyl‐Substituted Al Anion through Hydride‐Eliminating SNAr Reaction

Abstract: Reaction of an Al-centered anion with toluene proceeded to form CÀH cleaved product with a perfect metaselectivity and a relatively small kinetic isotope effect (KIE, k H / k D = 1.51). DFT calculations suggested a two-step reaction mechanism and electronically controlled meta-selectivity arising from the electron-donating methyl group. The reaction with other mono-substituted arenes was also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 63 publications
4
41
1
Order By: Relevance
“…Those reactions typically require forcing conditions or transition metal catalysts to proceed, they often give rise to two or more isomers, and these isomers can include benzylic products arising from competing C−H activations of toluene or xylene methyl groups. In the current study, the metallations of toluene and meta ‐xylene were found to occur selectively at a C‐position meta to a methyl group (yielding 4 and 6 ), as is often the case with the major isomer of product mixtures resulting from Al I (and Mg II [5f] ) induced arene metallations [7–9] . Although the formation of 5 also involves metallation at a site meta to one methyl group, there are no instances of a main group reagent selectively metallating ortho ‐xylene to give a 1‐metallo‐2,3‐dimethylphenyl product (as is 5 ).…”
Section: Methodssupporting
confidence: 53%
See 1 more Smart Citation
“…Those reactions typically require forcing conditions or transition metal catalysts to proceed, they often give rise to two or more isomers, and these isomers can include benzylic products arising from competing C−H activations of toluene or xylene methyl groups. In the current study, the metallations of toluene and meta ‐xylene were found to occur selectively at a C‐position meta to a methyl group (yielding 4 and 6 ), as is often the case with the major isomer of product mixtures resulting from Al I (and Mg II [5f] ) induced arene metallations [7–9] . Although the formation of 5 also involves metallation at a site meta to one methyl group, there are no instances of a main group reagent selectively metallating ortho ‐xylene to give a 1‐metallo‐2,3‐dimethylphenyl product (as is 5 ).…”
Section: Methodssupporting
confidence: 53%
“…[4] With respect to the latter, remarkable advances have come from the groups of Mulvey, Knochel, Hevia and others, who have developed a variety of "normal" oxidation state main group heterobimetallic systems, for example, turbo-Grignard reagents and turbo-Hauser bases, for the synergistic and selective deprotonation(s) of numerous unsaturated substrates. [5] In the past several years, low oxidation state p-block compounds have entered this arena, most notably from the groups of Harder, [6] Crimmin, [7] Aldridge and Goicoechea, [8] and Yamashita, [9,10] who have used either neutral or anionic nucleophilic aluminum(I) reagents for the activation of CÀH bonds in benzene, toluene and xylenes, both in the presence or absence of catalysts. These reactions proceed via formal oxidative addition of the C À H bond to an Al I center, and deliver varying degrees of product selectivity, depending on the Al I reagent and substrate employed.…”
mentioning
confidence: 99%
“…In the current study, the metallations of toluene and meta-xylene were found to occur selectively at a C-position meta to a methyl group (yielding 4 and 6), as is often the case with the major isomer of product mixtures resulting from Al I (and Mg II [5f] ) induced arene metallations. [7][8][9] Although the formation of 5 also involves metallation at a site meta to one methyl group, there are no instances of a main group reagent selectively metallating ortho-xylene to give a 1-metallo-2,3dimethylphenyl product (as is 5). That being the case, Crimmin and co-workers have reported that a Pd 0 catalyzed alumination of ortho-xylene yields the ortho-aluminated product as the minor isomer.…”
mentioning
confidence: 99%
“…Remarkably, the Ca-catalysed alumination of toluene occurs almost exclusively at the meta-position of the substrate, consistent with a mechanism involving nucleophilic attack of the aluminium reagent on an arene with an electrondonating substituent. 42,43 Recent studies have revealed that the C-H activation step also plays an important role in reactions that break strong C-O and C-F bonds. In the presence of palladium catalyst, C-O and C-F alumination reactions with Al-2 can also occur via a C-H activation process.…”
Section: C-h Aluminationmentioning
confidence: 99%